Dominant seismic noise sources in the Southern Ocean and West Pacific, 2000–2012, recorded at the Warramunga Seismic Array, Australia. Issue 10 (28th May 2014) - Reading, Anya M.; Koper, Keith D.; Gal, Martin; Graham, Leon S.; Tkalčić, Hrvoje; Hemer, Mark A.
Abstract Seismic noise is important in determining Earth structure and also provides an insight into ocean wave patterns and long‐term trends in storm activity and global climate. We present a long‐duration study of seismic noise focused on the Southern Ocean using recordings from the Warramunga Seismic Array, Northern Territory, Australia. Using high‐resolution analysis, we determine the seismic slowness and back azimuth of observed seismic noise, microseisms, at hourly intervals through over a decade (2000–2012). We identify three dominant sources of body wave (P) noise in the Southern Ocean which we interpret to originate from a South Atlantic source propagating as PP waves, and Kerguelen Island and Philippine Sea sources propagating as P waves. We also identify surface waves from around the Australian coast. All sources show distinct seasonality and a low, but discernable, interannual variability.